2014
DOI: 10.1093/trstmh/tru056
|View full text |Cite
|
Sign up to set email alerts
|

Human diarrhea infections associated with domestic animal husbandry: a systematic review and meta-analysis

Abstract: Domestic animal husbandry, a common practice globally, can lead to zoonotic transmission of enteric pathogens. However, this risk has received little attention to date. This systematic review and meta-analysis examines the evidence for an association between domestic exposure to food-producing animals and cases of human diarrhea and specific enteric infections. We performed a systematic review of available literature to examine domestic livestock and poultry as risk factors for diarrhea and applied pre-determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
171
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(186 citation statements)
references
References 44 publications
8
171
3
2
Order By: Relevance
“…This adds to the growing body of knowledge that existing WASH interventions that target improving water access, toilet/latrine access, and handwashing may not eliminate children's exposure to fecal contamination in the domestic environment. 9,10,22,23 Reported soil ingestion was the highest among children aged 6-24 months, which is consistent with previous studies evaluating child geophagy 10 and child mouthing behavior. 24 In addition, no soil ingestion was reported for children younger than 6 months, which is likely due to children being relatively inactive at this age.…”
Section: Discussionsupporting
confidence: 90%
“…This adds to the growing body of knowledge that existing WASH interventions that target improving water access, toilet/latrine access, and handwashing may not eliminate children's exposure to fecal contamination in the domestic environment. 9,10,22,23 Reported soil ingestion was the highest among children aged 6-24 months, which is consistent with previous studies evaluating child geophagy 10 and child mouthing behavior. 24 In addition, no soil ingestion was reported for children younger than 6 months, which is likely due to children being relatively inactive at this age.…”
Section: Discussionsupporting
confidence: 90%
“…First, it is possible that sick household livestock serve as an indicator for poor overall household health. A recent study from the same cohort showed that livestock disease reports were significantly associated with human disease reports within the same household (24), which is supported by previous studies of animal husbandry (35). A second possibility is that sick livestock serve as source of zoonotic pathogens in the household.…”
Section: Discussionsupporting
confidence: 53%
“…6,12 Existing studies show that contact with food-producing animals such as livestock and poultry increase the risk of diarrhea in children. 13 Studies have revealed several common enteric pathogen-animal combinations and identified positive associations between chicken ownership and transmission of Campylobacter spp. 14,15 and Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%